An exploration of coaching practices in leading South African companies - Attlee, Zia Delphine (My University, 2013)
This research uncovered the coaching practices of the leading South African companies. The objective of the study was to explore whether these companies use coaching in their organisations and to provide other South African organisations and coaches with an understanding of how the most successful South African companies manage the coaching process and whether they evaluate the outcomes of the coaching process. This study used an explanatory sequential mixed methods design. The quantitative phase consisted of an online questionnaire completed by 49 of the top 100 companies listed on the Johannesburg Stock Exchange (JSE). The qualitative phase involved semi-structured interviews with 11 of the top 100 JSE listed companies. Coaching programmes in the leading companies of South Africa have been in place for one to three years and are predominantly used for leadership development and performance management. The main recipients of coaching in these companies are executives, senior managers and up-and-coming talent. Leading South African companies integrate coaching with the organisation’s talent management strategy or the organisation’s business strategy. The leading South African companies select external coaches based on coaching experience, business experience, recommendations and qualifications and contract them to work with executive and senior management levels. They also use internal coaches but mostly to coach up-and-coming talent and graduates. They do not enforce the supervision of coaches and engaging in supervision is mostly decided by the coaches themselves. Measuring of coaching outcomes is important to the leading companies of South Africa and therefore most of these companies measure its impact. This research provides key insights into the coaching practices of the leading South African companies. The research also provides guidance to coaches and organisations in South Africa on how coaching can be used to develop individuals and organisations.
Thesis (M.M. (Business Executive Coaching))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Executives; Coaching